Rocking Response of Slender Freestanding Building Contents in Fixed-Base and Base-Isolated Buildings - Linde, Scott A. (My University, 2016)
The primary seismic response mode of freestanding slender building contents is rocking. Rocking is one of the most damaging response modes due to large accelerations at impact and the possibility of toppling. This study investigates the rocking response of contents within fixed-base and base-isolated buildings so that better-informed decisions can be made, either at the design stage for new structures or during the performance evaluation for existing structures, to mitigate the effects of the destructive rocking behaviour and consequently minimize injury, economic loss, and downtime. A 3D model of a hospital building was created in OpenSees and analyzed to obtain floor accelerations for a suite of 20 broadband ground motions. These motions were then used as input to compute the rocking responses of many building contents. The rocking responses were compared and contrasted to determine the effect of the block’s size, slenderness, floor level, and placement within a level. The rocking response of contents in buildings isolated with lead plug and triple friction pendulum bearings were compared to the fixed-base building to determine the effectiveness of isolation as a means to control rocking. Fragility curves were also created for the fixed-base and isolated buildings. The vertical component of the floor accelerations had little effect on the rocking response of contents. The significance of this is that the location of an object on a given story does not affect its rocking response. However, higher vertical accelerations did increase the likelihood of the object lifting off the floor. The rocking response of stocky contents increased from one story to the next, but as the slenderness increased this transition became less evident. Base isolation was found to be effective at reducing both the likelihood to uplift and overturn. The longer period systems provided superior protection despite the long period pulse like motion while the damping of the systems had little effect on the rocking response.
Keywords: Rocking; Overturning; Nonstructural Components; Building Contents